North American Practice-Based Recommendations for Transjugular Intrahepatic Portosystemic Shunts in Portal Hypertension - Boike, Justin R.; Thornburg, Bartley G.; Asrani, Sumeet K.; Fallon, Michael B.; Fortune, Brett E.; Izzy, Manhal J.; Verna, Elizabeth C.; Abraldes, Juan G.; Allegretti, Andrew S.; Bajaj, Jasmohan S.; Biggins, Scott W.; Darcy, Michael D.; et al. (Clinical gastroenterology and hepatology, 2022)
Complications of portal hypertension, including ascites, gastrointestinal bleeding, hepatic hydrothorax, and hepatic encephalopathy, are associated with significant morbidity and mortality. Despite few high-quality randomized controlled trials to guide therapeutic decisions, transjugular intrahepatic portosystemic shunt (TIPS) creation has emerged as a crucial therapeutic option to treat complications of portal hypertension. In North America, the decision to perform TIPS involves gastroenterologists, hepatologists, and interventional radiologists, but TIPS creation is performed by interventional radiologists. This is in contrast to other parts of the world where TIPS creation is performed primarily by hepatologists. Thus, the successful use of TIPS in North America is dependent on a multidisciplinary approach and technical expertise, so as to optimize outcomes. Recently, new procedural techniques, TIPS stent technology, and indications for TIPS have emerged. As a result, practices and outcomes vary greatly across institutions and significant knowledge gaps exist. In this consensus statement, the Advancing Liver Therapeutic Approaches group critically reviews the application of TIPS in the management of portal hypertension. Advancing Liver Therapeutic Approaches convened a multidisciplinary group of North American experts from hepatology, interventional radiology, transplant surgery, nephrology, cardiology, pulmonology, and hematology to critically review existing literature and develop practice-based recommendations for the use of TIPS in patients with any cause of portal hypertension in terms of candidate selection, procedural best practices and, post-TIPS management; and to develop areas of consensus for TIPS indications and the prevention of complications. Finally, future research directions are identified related to TIPS for the management of portal hypertension.